Base-Catalyzed Addition of Ketones to Alkynes as a Key Step in the One-Pot Synthesis of 1-Formyl-2-pyrazolines - Schmidt, Elena Yu.; Ivanova, Elena V.; Tatarinova, Inna V.; Semenova, Nadezhda V.; Ushakov, Igor A.; Trofimov, Boris A. (Synthesis, 2015)
The reaction of ketones with alkynes in the presence of potassium tert-butoxide and dimethylsulfoxide followed by the treatment of the reaction mixture with hydrazine hydrate and formic acid leads to 2-pyrazoline-1-carbaldehydes in up to 81% yield.
Keywords: ketones; alkynes; 1-formyl-2-pyrazolines; superbases; vinylation